KURIKULUM PENDIDIKAN MENURUT IBNU SINA DAN RELEVANSINYA TERHADAP PENGEMBANGAN KURIKULUM PENDIDIKAN - Nur Zaini (Fakultas Agama Islam Universitas Billfath, 2019)
Ibnu Sina offers curriculum concepts as well as modern curriculum concepts, namely a curriculum that not only contains a number of subjects that must be taught, but also is accompanied by an explanation of the objectives of these subjects to be given. Other than that, Ibn Sina also stressed the need for the principle of link and macth between subjects given with the interests and talents of students. And the suitability of the subjects with the professional demands of the market (the community).